2016
DOI: 10.1142/s0578563416400234
|View full text |Cite
|
Sign up to set email alerts
|

Behavior from Tsunami Recorded in the Multimedia Sources at Kesennuma City in the 2011 Tohoku Tsunami and Its Simulation by Using the Evacuation Model with Pedestrian—Car Interaction

Abstract: The evacuation behavior observed in Kesennuma City, Tohoku, Japan during the Great East Japan Earthquake and Tsunami and a corresponding evacuation simulation are presented. We first organized the damage and evacuation behaviors observed in the target area using the results of previous studies and official surveys. In addition, we compiled all available multimedia sources recording evacuation behavior during the 2011 event to identify the precise temporal and spatial details of the evacuation behavior. Then, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…To reveal this type of potential risk during an evacuation, tsunami evacuation simulations, which have recently been studied, are essential tools for the quantitative evaluation of future evacuation events, although accurate simulations require further research on human behavioral characteristics during an evacuation [Mas et al, 2015;Makinoshima et al, 2016]. Every evacuation countermeasure discussed above is important and effective for casualty mitigation during future tsunami events; however, the most important lesson learned from the Great East Japan Earthquake and Tsunami is the strenuous effort required in daily life to prepare for future tsunamis, even when many years have passed since the last event.…”
Section: Inland Evacuationmentioning
confidence: 99%
“…To reveal this type of potential risk during an evacuation, tsunami evacuation simulations, which have recently been studied, are essential tools for the quantitative evaluation of future evacuation events, although accurate simulations require further research on human behavioral characteristics during an evacuation [Mas et al, 2015;Makinoshima et al, 2016]. Every evacuation countermeasure discussed above is important and effective for casualty mitigation during future tsunami events; however, the most important lesson learned from the Great East Japan Earthquake and Tsunami is the strenuous effort required in daily life to prepare for future tsunamis, even when many years have passed since the last event.…”
Section: Inland Evacuationmentioning
confidence: 99%
“…The 2011 event revealed that car usage, which exceeded the road capacities of local communities, caused severe traffic jams and tsunami casualties [21,22]. Moreover, the same problem was reported in the recent 2016 Fukushima Tsunami [23].…”
Section: Introductionmentioning
confidence: 82%
“…Figure 1 illustrates the location of the study area and the geographical features of the central urban area for a simulated tsunami [29,30]. Here, the geographical features are those before the 2011 tsunami, and the simulated tsunami was validated in a previous study [22]. As shown in Figure 1a,b, the study area is located in the northeast coastal part of Japan, which experienced a devastating tsunami that reached a height of over 10 m, as illustrated in Figure 1c.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations